The influence of emotional intelligence on learning burnout in Chinese arts college students: The chain mediating effect of self-acceptance and perceived stress - Meng Zhang; Lay, Yoon Fah (Frontiers Media S.A., 2025)
Introduction: Art college students are under special pressure from a few sources, including study, employment, friends, emotions, family relations and other aspects. This can lead to a reasonable degree of learning burnout among art college students, which will have a negative impact on their physical and mental health, as well as their study and employment. However, there is a paucity of empirical studies on learning burnout among art students. Furthermore, the factors and mechanisms that contribute to learning burnout among art students remain unclear. The purpose of this study was to examine the relationship between emotional intelligence and learning burnout in Chinese art college students, and to identify the role of self-acceptance and perceived stress as sequential mediators. Methods: This study employed a completely random survey of three art universities in China to investigate the status of emotional intelligence, selfacceptance, perceived stress and learning burnout among art students and their relationships. The data was analyzed using an independent sample t-test and structural equation modelling. Results: A total of 678 valid samples were obtained from a study of Chinese art students. No significant differences were observed in the scores of emotional intelligences, self-acceptance, perceived stress, and learning burnout among participants of different genders. The results of the structural equation modelling indicated that emotional intelligence was negatively associated with learning burnout (β = −0.282, p < 0.001). The results indicated that self-acceptance (β = −0.140, p < 0.001) and perceived stress (β = −0.072, p < 0.001) had independent mediating effects. Furthermore, self-acceptance and perceived stress exhibited sequence mediating effects (β = −0.039, p < 0.001). Conclusion: The results of the study confirm that emotional intelligence is a significant factor in the learning burnout of art students. Furthermore, the findings demonstrate the mediating effect of self-acceptance and perceived pressure on this relationship. The findings provide a novel explanation for the mechanism underlying college students’ learning burnout.